2018
DOI: 10.3329/bjms.v17i4.38334
|View full text |Cite
|
Sign up to set email alerts
|

NS-1 antigen positive Dengue Infection and molecular characterization of Dengue Viruses in a private Medical College Hospitalin Dhaka, Bangladesh

Abstract: Introduction: Detection of dengue virus infection as soon as possible is critical for management of dengue virus infected patients. Immuno-chromatographic (ICT) tests are easy, cost effective method for dengue virus antigen detection.The sensitivity and specificity of ICT should compare with a gold standard test like RT-PCR. Aim of this study was to compare two test methods (ICT and RT-PCR), observe dengue serotype and seasonal impact on dengue infection.Methodology & result: The patients of Ibn Sina Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The study conducted in Bangladesh mentioned that DEN 2 serotype was most prevalent in their population 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted in Bangladesh mentioned that DEN 2 serotype was most prevalent in their population 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar dengue symptoms as fever, headache, joint pain, muscle pain and rash are observed in other febrile illnesses as Chikungunya/Zika viral infections 8 . These infections are also transmitted by the dengue vector, Aedesaegypti and Aedes albopictus 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, clinical incidence of dengue peaked at approximately 6,500 cases, apparently due to circulation of the DENV-3 serotype in the country, which had been notably absent during 2013-2017 [43]. A recently published study that examined dengue isolates over the three-year period 2015-2017 confirmed co-circulation of DENV-1 and DENV-2 serotypes in the nation's capital and largest city, Dhaka, suggesting the absence of DENV-3 and DENV-4 [29]. The epidemiology of dengue transmission in Bangladesh is therefore complex and fluid.…”
Section: Dengue In Bangladeshmentioning
confidence: 99%
“…Several variable factors, such as sample collection time, storage and transportation, contribute to the differing sensitivity of tests performed under separate circumstances. Quite a few studies have highlighted the use of NS1 antigen and anti-NS1 antibody as a key dengue diagnostic device as it has the capacity to differentiate different serotypes and also helps to distinguish between primary and subsequent infections [27][28][29]. However, possibilities for improvement remain, with, for example, a reliable, cost-effective, highly specific and ultra-sensitive tool yet to be designed.…”
Section: Dengue Control: Current Schemes and Their Limitationsmentioning
confidence: 99%
“…The incidence and transmission of dengue is in uenced by a variety of factors such as uncontrolled population growth, urbanization, deterioration in waste management systems, changes in the climate and lack of effective vector control [12]. Water storage practice as the water supplies are inadequate mainly in metropolitan cities is also regarded as a major contributor to dengue epidemics [13].…”
Section: Introductionmentioning
confidence: 99%